2013
DOI: 10.1038/jp.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Timing of prophylactic antibiotic at cesarean section: a double-blinded, randomized trial

Abstract: OBJECTIVE:The purpose was to determine the effect of the timing of prophylactic antibiotics for cesarean section on post-operative infectious complications. STUDY DESIGN: This was a prospective, double-blinded, randomized controlled trial in which patients were randomized to receive cefazolin or clindamycin either before skin incision or after cord clamp. The primary outcome was maternal infectious morbidity at 6 weeks postpartum, a composite infectious outcome, which included endometritis, urinary tract infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We included 18 RCTs comparing the application of prophylactic antibiotics before vs. after cord clamping (13,(17)(18)(19)(20)(21)(22)(23)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were conducted in the USA (17,20,29,(32)(33)(34)(35), Turkey (37), Austria (36), India (28,30), Iran (18,21), Egypt (31), Tunisia (19), Sudan (22), Italy (23) and China (13). The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 18 RCTs comparing the application of prophylactic antibiotics before vs. after cord clamping (13,(17)(18)(19)(20)(21)(22)(23)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The studies were conducted in the USA (17,20,29,(32)(33)(34)(35), Turkey (37), Austria (36), India (28,30), Iran (18,21), Egypt (31), Tunisia (19), Sudan (22), Italy (23) and China (13). The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The indication for the cesarean section, number of randomized women in treatment groups, antibiotic class, agent and dosing scheme of the administered antibiotic(s) and the actual time when the antibiotic(s) were given, are presented in Table S1. In brief, 13 studies included women with elective cesarean section solely (13,(17)(18)(19)(20)22,(29)(30)(31)(32)(33)36,37), two studies reported that more than 75% of women received elective cesarean section (21,28), and three studies were focused on non-elective cesarean section (23,34,35). The majority of studies administered a first-generation cephalosporin (cefazolin 1 g, cefazolin 2 g or cefathiamidin 2 g) (13,18,19,21,29,(31)(32)(33)(34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there is no prospective study investigating the mid- or long-term effect on the infant. (2) The results are not universal with some studies showing no difference in maternal complications regardless of whether antibiotics are given before skin incision or after cord clamping [4,68,69,70]. (3) The rate of postoperative morbidity in the USA is much higher than in other developed countries―probably due to high rates of obesity and diabetes.…”
Section: Obstetrical Antibiotic Indications During Pregnancymentioning
confidence: 99%
“…postoperative antimicrobial prophylaxis is unnecessary as it increases cost and causes drug resistance with resistant bacteria. 27 There is insufficient evidence concerning timing of administration (preoperative versus after cord clamping) of antibiotic prophylaxis for caesarean section. Nearly all published trials since 1978 have administered the antimicrobial drug immediately after the cord is clamped.…”
Section: Introductionmentioning
confidence: 99%